PENGARUH METODE ODOV TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA SEKOLAH DASAR - Aprianti, Nia; Herniawati, Ani; Purbayani, Rini (Jurnal Intisabi, 2026)
This study aims to investigate the impact of the ODOV (One Day, One Vocabulary) method on the English speaking ability of elementary school students. This study uses a quantitative method with a Pre Experiment approach with a One-Group Pretest-Posttest design. The subjects of the study were fourth-grade students of SDN 4 Bojongmengger. Data were collected through pretest and posttest. The results of the descriptive analysis showed an increase in the average score of students' language speaking ability from 63.57 (pretest) to 79.04 (posttest). The Shapiro-Wilk normality test showed that the data was normally distributed, and the results of the Paired Sample t-test showed a Sig. (2-tailed) value of 0.000 <0.005. This proves that there is a significant effect of the ODOV method on students' English speaking ability. Thus, the ODOV method is effective in improving English speaking ability of fourth grade students at SDN 4 Bojongmengger.